PELATIHAN PENGGUNAAN APLIKASI GEOGEBRA DALAM MENYELESAIKAN TURUNAN FUNGSI REAL BAGI SISWA SMA 4 SIGI - Lusiyanti, Desy; Selvy Musdalifah; Iman Al Fajri; Andri (Jurusan Farmasi FMIPA Universitas Tadulako, 2024)
The training on the use of the GeoGebra™ application at SMA 4 Sigi aimed to enhance students' understanding of the concept of derivatives of real functions through an interactive and technology-based learning approach. GeoGebra™ was chosen as a tool due to its capability to visualize function graphs and their derivatives, thus facilitating students' comprehension of complex mathematical concepts. This training involved 40 students, beginning with basic GeoGebra™ introductions and concluding with practical applications in solving derivative problems. The results of the training showed a significant improvement in students' understanding and skills, as evidenced by an average increase of 25 points in post-test scores compared to pre-test scores. Additionally, feedback from students indicated that 90% felt more confident and found GeoGebra™ easy to use, and were satisfied with the learning method implemented. The use of GeoGebra™ also successfully fostered students' interest in exploring more mathematical topics through visualization approaches. The success of this training highlights the importance of integrating technology into education to enhance learning quality and students' skills in solving mathematical problems. It is recommended that this training becomes a regular program with a broader scope of topics to support the continuous development of students' technological and academic abilities.